PERANCANGAN MARKET BASKET ANALYSIS MENGGUNAKAN ASSOCIATION RULE UNTUK PENDUKUNG PROMOSI PADA SISTEM PENJUALAN SUN YOUNG CELL - Rina Halim; Amroni .; Pareza Alam Jusia (Jurnal PROCESSOR, 2017)
Organized sales transactions information processing is needed to provide an overview and analysis to support strategic decision making for the organization. This study aims to design Market Basket Analysis for sales system at Sun Young Cell as a sales transaction information processing application which can provide analytical results representing sales rates according to trends in certain product sales. The technique used is association rule that describes the patterns of transaction by using rules to support decision making process.